PENGARUH BIAYA OPERASIONAL TERHADAP LABA BERSIH PT BUKIT ASAM TBK TAHUN 2009-2023 - Putri, Sakila; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines the effect of operational costs on net profit at PT Bukit Asam Tbk over the period 2009 to 2023. The method applied is associative quantitative research with a simple linear regression approach. Secondary data were obtained from annual financial reports published by the company. The sample consists of 15 years of financial data covering the study period. Statistical analysis was conducted using SPSS software, encompassing classical assumption tests, correlation analysis, coefficient of determination, and hypothesis testing through t-test and F-test. The results show that operational costs have a significant positive effect on net profit, indicated by a correlation coefficient (R) of 0.768, a coefficient of determination (R²) of 0.590, and a t-count value of 4.325 with significance 0.001 < 0.05. This finding implies that approximately 59% of the variation in net profit can be explained by changes in operational costs. The regression equation obtained is Y = 239,739.370 + 0.321X, meaning every increase of one unit in operational cost tends to raise net profit by 0.321 units.